Treatment with pemafibrate ameliorates fatty liver index and atherogenic lipid profiles in Japanese patients with type 2 diabetes mellitus - Suzuki, Toru; Sato, Tatsuya; Tanaka, Marenao; Nakata, Kei; Endo, Keisuke; Aida, Hiroki; Kawaharata, Wataru; Hosaka, Itaru; Umetsu, Araya; Ogawa, Toshifumi; Akiyama, Yukinori; Furuhashi, Masato (Frontiers in Endocrinology, 2025)
BackgroundPemafibrate, a selective peroxisome proliferator-activated receptor α modulator, ameliorates hypertriglyceridemia. We investigated the effects of pemafibrate on steatotic liver disease (SLD) in relation to various atherogenic lipid profiles.MethodsThirty-nine Japanese patients with both type 2 diabetes mellitus (T2DM) and hypertriglyceridemia (men/women: 24/15, mean age: 58.2 years, median duration of diabetes: 5.0 years) were treated with 0.2 mg/day of pemafibrate for 12 months (M). SLD was estimated by fatty liver index (FLI), which is calculated by using waist circumference, body mass index and levels of triglycerides and γ-glutamyl transpeptidase.ResultsTreatment with pemafibrate significantly increased mean levels of high-density lipoprotein cholesterol (HDL-C) (baseline/3M/6M/12M: 46/55/55/54 mg/dL) and decreased median levels of triglycerides (baseline/3M/6M/12M: 211/112/99/98 mg/dL), non-HDL-C (146/128/125/121 mg/dL), small dense low-density lipoprotein cholesterol (45/33/30/30 mg/dL) and remnant-like particle cholesterol (8.1/2.6/2.3/2.4 mg/dL). There was no significant change in hemoglobin A1c level over time. FLI (mean ± standard deviation: 68.1 ± 21.9 vs. 39.6 ± 25.0, P < 0.001), but not FIB-4 index as a marker of hepatic fibrosis (median [interquartile range]: 1.04 [0.78-1.39] vs. 1.01 [0.68-1.36], P = 0.909), was significantly decreased by treatment with pemafibrate for 12M, and the proportion of patients with metabolic dysfunction-associated SLD (MASLD) was significantly decreased from 92.3% (baseline) to 61.5% (12M).ConclusionsPemafibrate ameliorates MASLD estimated by FLI in addition to various atherogenic lipid profiles in Japanese hypertriglyceridemia patients with T2DM in the past mean 5 years. An early intervention with pemafibrate might contribute to prevention of the development of MASLD and atherosclerotic cardiovascular disease.